Clinical features of Chinese patients in different age groups with spontaneous intracerebral hemorrhage based on multicenter inpatient information. (2nd August 2020) - Wang, Pingping; Sun, Yong; Yi, Danhui; Xie, Yanming; Luo, Yumin
ABSTRACT: Background: Patients with spontaneous intracerebral hemorrhage (ICH) have poor functional outcomes. This study investigated the status of hospitalized patients with ICH based on multicenter inpatient information. Methods: We analyzed data from the hospital information systems (HISs) of 14 tertiary hospitals, including 6 Chinese medicine hospitals and 8 western hospitals from 7 provinces and 2 municipalities. The inclusion criteria were age ≥25 years and radiologically confirmed spontaneous ICH within two weeks of symptom onset. Age groups were as follows: 25–44, 45–59, 60–74, 75–89, 90 and over 90 years old. Data are presented as the proportion (%), median (interquartile range) or mean (standard deviation). Descriptive statistical analyses were conducted to analyze demographic features, lengths of hospital stay, hospitalization expenses, hematoma locations, mortality and major comorbid conditions or complications. Results: Patients were recruited from October 2003 to September 2011. A total of 9475 inpatients were recruited from 14 Class III Grade A hospitals. Baseline characteristics included a mean age of 58 (20) years old and 37.2% female (3303). The largest number of ICH patients were in the 44–59-year-old group. The ratio of males to females in the 25–44-year-old age group was 2.36:1, which was the highest of all groups; the lowest male to female ratio was 1.56:1 in the 45–59-year-old age group. The ratios of males to females in the 60–74, 75–89 and ≥90-year-old age groups were 1.60:1, 1.62:1 and 1.64:1, respectively. The proportion of males in all age groups was higher than that of females, significantly greater in the 25–44-year-old age group (P < 0.001). The lengths of hospital stay ranged from 15 to 28 days. The hospitalization expenses of the 25–44-year-old patients were 50, 000–100, 000 RMB, and the costs of the remaining age groups were 10, 000–20, 000 RMB. Basal ganglia/thalamic hemorrhage was the most common site of ICH in different age groups. Lobar and multiple locations were higher in those aged >75 years. Hypertension was the primary comorbid condition in all age groups, and it showed a rising trend with increasing age. The second most common comorbidity in the 25–44-year-old age group was vascular abnormality, while in the other age groups, comorbidities included cerebral infarction, dyslipidemia, coronary heart disease, diabetes mellitus and arrhythmia. Mortality increased with age; mortality for those under the age of 74 years fluctuated between 4.09% and 5.93%, whereas in those in the 75–89 and ≥90-year-old age groups, mortality was 13.34% and 34.09%, respectively. Conclusions: As age increased, the length of hospital stay, financial burden and mortality due to ICH increased. Different age groups had different distributions of neuroimaging features, major comorbid conditions or complications.